The Effect of Cognitive Diagnostic Assessment and Non-Cognitive Diagnostic Assessment on Social Studies Learning Motivation of Grade VIII Students at UPT SMPN 2 Binamu, Jeneponto Regency - Mantasiah, Mantasiah; Syarifuddin, Syarifuddin; Fahreza W, Muhammad (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study aims to determine and analyse 1). The effect of cognitive diagnostic assessment on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 2). The effect of non-cognitive diagnostic assessment on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 3). The simultaneous influence of cognitive diagnostic assessment and non-cognitive diagnostic assessment on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency; and 4). To determine and analyse the dominant variables that influence the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. This research uses a quantitative research approach. The research was conducted on eighth-grade students at SMPN 2 Binamu, Jeneponto Regency, with a population consisting of all eighth-grade students at SMPN 2 Binamu, Jeneponto Regency, comprising five classes, namely: VIII 1, VIII 2, VIII 3, VIII 4, and VIII 5, with a total of 154 students. The sampling technique used was purposive random sampling, with 10 students representing each class, resulting in a sample size of 50 students. Data collection was conducted using questionnaires, and data analysis was performed using multiple regression analysis, t-test, and F-test. The results of the study are as follows: 1) Cognitive Diagnostic Assessment (X1) has a positive and significant effect on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 2) Non-cognitive Diagnostic Assessment (X2) has a positive and significant effect on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 3). Cognitive Diagnostic Assessment (X1) and Non-Cognitive Diagnostic Assessment (X2) together have an effect on Social Studies Learning Motivation (Y) among eighth-grade students at UPT SMPN 2 Binamu, Jeneponto District. 4). The most dominant variable influencing the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto District, is cognitive diagnostic assessment.